Treatments for partial remission of major depressive disorder: a systematic review and meta-analysis - Marlies E Brouwer; Gert J Geurtsen; Damiaan A J P Denys; Joost Gülpen; Eva A M van Dis; Claudi L Bockting (BMJ Mental Health)
Question Partial remission of major depressive disorder (MDD) is a debilitating and distressing clinical state related to chronicity, morbidity and relapse. Although one-third of patients remit partially, evidence for treatment efficacy is unclear. We provide an overview of treatment options and their efficacy.Study selection and analysis Embase, PsycINFO, Medline and SCOPUS were systematically searched through February 2023. Included were randomised controlled trials (RCTs) examining any treatment in patients with partially remitted MDD aged 13–65 years, reporting data on severity, remission or relapse.Findings Seven RCTs examining psychotherapy including 1024 patients were eligible. There were not enough RCTs to examine effects of pharmacotherapy. Psychotherapy was associated with lower depressive symptom severity at post-treatment (Hedges’ g=0.50; 95% CI 0.23 to 0.76), but not at follow-up up to 1 year (Hedges’ g=0.36; 95% CI −0.30 to 1.02) or longer (Hedges’ g=0.02; 95% CI −0.09 to 0.12). Psychotherapy was associated with superior remission rates at post-treatment (OR 2.57; 95% CI 1.71 to 3.87) and follow-up 6 months or longer (OR 1.75; 95% CI 1.21 to 2.53), although not with improved relapse rates at post-treatment (OR 0.17; 95% CI 0.01 to 4.83) or follow-up 6 months or longer (OR 0.46; 95% CI 0.21 to 1.03). Overall methodological quality was poor.Conclusions Psychotherapy targeting partial remission may be effective in lowering depressive symptom severity and patients may potentially achieve full remission twice as likely. Yet, long-term and prophylactic effects are lacking. Given the risk of chronicity, more high-quality RCTs are needed.PROSPERO registration number CRD42020188451.